Dora Madueño and the first Peruvian women mayors in 1945 - Bedoya, Carlos (2019)
In 1945, after Jose Luis Bustamante y Rivero came to power, four women served as mayors for the first time, elected within the transitional municipal Councils established in regional electoral assemblies according to the Law N.° 10233. Dora Madueño Mayor of Huancane, Angelica Zambrano Mayor of Urubamba, Eva Morales Deputy Mayor of Arequipa, and Susana Leon Deputy Mayor of Matucana. All elected between October and November of that year, but have been erased of the historical memory. The article provides the first register of these facts, as well as offering an examination of the political, legal and gender aspects that made possible those experiences. In particular, in the case of Dora Madueño (1916-2013), the first woman mayor in Peru.